COMMUNITY-LEVEL SOCIAL TENSIONS SURROUNDING ZIMBABWEAN MIGRATION IN SOUTH AFRICA - KHABO, SIBONAKALISIWE ZODWA (Sosiohumaniora, 2026)
The presence of Zimbabwean migrants in South African communities has led to a rise in public debates and emotive sentiments over the years. Although Zimbabwean migration is not a new phenomenon in the region, public debates and community sentiments often reflect that it has led to an increase in anxiety over belonging, access to services and social coexistence. These disgruntlements have been the main cause behind conflicts between migrants and South African locals in communities, Zimbabwean migration is no longer viewed in the humanitarian lens but rather as threat to locals’ job security as well as social cohesion.  Using the social constructivist framework, the study argues that social tensions are not shaped entirely by economic or social circumstances but are a result of socially constructed perceptions of threat and outsider status. The study employs qualitative content analysis of media reports, civil society records and existing scholarly works to establish prevalent narratives that portray Zimbabwean migrants as exacerbating unemployment, criminal activity and the strain on public resources. The results indicate that local conflicts often arise when migrants are labelled as the cause of wider socio-economic dissatisfaction. By focusing on local social dynamics, the article contributes to migration studies in International Relations by highlighting how local social dynamics shape the reception of migrants.